2019
DOI: 10.1016/j.joca.2018.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response relationship between ambulatory load magnitude and load-induced changes in COMP in young healthy adults

Abstract: The results of this study provide important evidence of a dose-response relationship between ambulatory load magnitude and load-induced changes in sCOMP. Our data suggests that in normal weight persons sCOMP levels are more sensitive to increased than to reduced load. The experimental framework presented here may form the basis for studying the relevance of the dose-response relationship between ambulatory load magnitude and load-induced changes in biomarkers involved in metabolism of healthy articular cartila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 39 publications
(33 reference statements)
1
31
1
Order By: Relevance
“…Cheleschi et al [15] demonstrated a reduction of β-catenin protein expression in OA chondrocytes exposed to 3 h of low sinusoidal HP (1-5 MPa), while no consistent load-dependent changes in total or active β-catenin-levels were observed by Praxenthaler et al [69] after the application of a single dynamic compression-episode. In the present study, we partially confirm these results observing an increased β-catenin protein expression in OA chondrocytes upon application of a static continuous HP of 10 MPa, while its activation was limited in physiological HP-exposed cells (1)(2)(3)(4)(5). We further hypothesize that the effect of mechanical loading or, specifically, of HP on Wnt/β-catenin pathway could be mediated by miRNA.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Cheleschi et al [15] demonstrated a reduction of β-catenin protein expression in OA chondrocytes exposed to 3 h of low sinusoidal HP (1-5 MPa), while no consistent load-dependent changes in total or active β-catenin-levels were observed by Praxenthaler et al [69] after the application of a single dynamic compression-episode. In the present study, we partially confirm these results observing an increased β-catenin protein expression in OA chondrocytes upon application of a static continuous HP of 10 MPa, while its activation was limited in physiological HP-exposed cells (1)(2)(3)(4)(5). We further hypothesize that the effect of mechanical loading or, specifically, of HP on Wnt/β-catenin pathway could be mediated by miRNA.…”
Section: Discussionsupporting
confidence: 88%
“…Articular cartilage is constantly exposed to a wide range of static and dynamic cycles of loading that can vary from 0.7 to 20 MPa depending on body weight, posture, and physical activity [1][2][3]. Moderate loads are safe and contribute to maintain cartilage homeostasis and integrity, while excessive or static stresses could be deleterious, inducing its degradation, and contributing to the onset and the progression of osteoarthritis (OA) [4,5]. At the cellular level, a dynamic physiological compression promotes chondrocyte proliferation and activity, whereas injurious static stress induces opposing, detrimental effects on cell anabolism reducing the synthesis of extracellular matrix (ECM) components [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Research examining the effect of acute changes in body weight on sCOMP levels during walking exercise also suggest that catabolic activity occurs at a greater rate in loaded versus unloaded walking conditions (Denning et al, 2015). A more recent investigation examining healthy participants, also reports that increasing body weight by 20% (using a weighted vest) resulted in a significant increase in sCOMP levels after 30 minutes of walking exercise, as compared to exercise completed using 20% unweighted or normal body weight conditions (Herger et al, 2019).…”
Section: Introductionmentioning
confidence: 92%
“…MMP serum levels are usually low in healthy individuals and increasing levels have been reported in arthritic patients 28 . Serum concentrations of MMP‐1, MMP‐3, and MMP‐9 are sensitive to loading with increasing values after, for example, resistive exercise (MMP‐1), 29 walking (MMP‐3 only), half‐marathon, marathon, and ultra‐marathon running 30‐32 . The expression of MMPs is usually regulated by cytokines such as tumor necrosis factor‐alpha (TNF‐α) which can be elevated after exercise 33 .…”
Section: Introductionmentioning
confidence: 99%
“…28 Serum concentrations of MMP-1, MMP-3, and MMP-9 are sensitive to loading with increasing values after, for example, resistive exercise (MMP-1), 29 walking (MMP-3 only), half-marathon, marathon, and ultra-marathon running. [30][31][32] The expression of MMPs is usually regulated by cytokines such as tumor necrosis factor-alpha (TNF-α) which can be elevated after exercise. 33 Leong et al 34 reported an increase in MMP-3 messenger RNA (mRNA) expression as early as 6 hours after immobilization using hind-limb unloading in rats followed by increased enzyme activity starting after 1 day of immobilization and both lasting until 21 days of immobilization.…”
mentioning
confidence: 99%